2019
DOI: 10.1002/ece3.4869
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics reveals high connectivity of giant panda populations across human disturbance features in key nature reserve

Abstract: The giant panda is an example of a species that has faced extensive historical habitat fragmentation, and anthropogenic disturbance and is assumed to be isolated in numerous subpopulations with limited gene flow between them. To investigate the population size, health, and connectivity of pandas in a key habitat area, we noninvasively collected a total of 539 fresh wild giant panda fecal samples for DNA extraction within Wolong Nature Reserve, Sichuan, China. Seven validated tetra‐microsatellite markers were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…However, in our estimation, G350 and S210 did not completely separate the big population into different subpopulations, which means giant pandas may cross these roads. Our results were supported by a recent large genetic study conducted in Wolong reserve (Qiao et al, 2019 ); Qiao et al ( 2019 ) found no significant genetic boundaries exists within panda population despite the national road G350 that bisects the Wolong nature reserve. They recorded four giant panda road‐crossing events within 1 year, indicating giant panda populations may be better connected than previously thought.…”
Section: Discussionsupporting
confidence: 88%
“…However, in our estimation, G350 and S210 did not completely separate the big population into different subpopulations, which means giant pandas may cross these roads. Our results were supported by a recent large genetic study conducted in Wolong reserve (Qiao et al, 2019 ); Qiao et al ( 2019 ) found no significant genetic boundaries exists within panda population despite the national road G350 that bisects the Wolong nature reserve. They recorded four giant panda road‐crossing events within 1 year, indicating giant panda populations may be better connected than previously thought.…”
Section: Discussionsupporting
confidence: 88%
“…Demographics for all pandas sampled in this study are shown in Table S1. Seven tetra-microsatellites including GPL-60, gpz-47, gpz-20, GPL-44, GPL-29, GPL-53, and gpz-6 were used to distinguish the wild individuals, and this DNA analysis was performed by Qiao et al, therefore the samples of wild giant pandas were from their research (Table S2) [25].…”
Section: Methodsmentioning
confidence: 99%
“…Eighteen fresh samples with mucosa were collected from 18 pandas which lived in the Wolong National Nature Reserve (wild group) based on freshness level. Individual genotypes were identified by Qiao et al (Qiao et al, 2019). The identification information is provided in Table 1.…”
Section: Sample Collectionmentioning
confidence: 99%